The Theory of Ecological Modernization: Central Ideas and Critical Insights - Rinkevičius, Leonardas (Sociologija. Mintis ir veiksmas, 2015)
The aim of the article is to discuss the theoretical paradigm of ecological modernization which represents one of the attempts to theorize the issues of enviromental care that only recently became an object of sociological analysis (Catton ir Dunlap, 1979; Buttel, 1987). The article is being developed in a few directions. First, the author develops a comparative analysis of the main sociological perspectives on the environmental care: ecological modernization (Mol, 1995; Weale, 1992; Hajer 1995; Spaargaren, 1997; Rinkevičius, 1998), the theory of risk society and reflexive modernization (Beck, 1992; Beck, Giddens ir Lash 1994), conception of self-purposive capitalistic production (Schnaiberg, 1980) and ecological socialism (Pepper, 1993; Dickens, 1992). Second, in developing such a comparative analysis, the author critically discusses  the different theories by concerning both the environmental problems that contemporary societies face and the changes that the societies undergo in the spheres of values and institutions.
Keywords: environmental care; sociology of environmental care; theory of ecological modernization